Tear-film imaging measurements of the lipid and muco-aqueous layers and their association with dry eye disease signs and symptoms in adults: A pilot, prospective, cross-sectional study at a tertiary eye care center - Isaac M. Tessone; Richard B. Rosen; Hernan Rios; Masako Chen; Alice Chandra Verticchio Vercellin; Brent A. Siesky; Paul A. Sidoti; Kira Manusis; Anna Fabczak-Kubicka; Keren Wood Shalem; Gal Antman (PLoS ONE, 2026)
The purpose of this study was to assess tear film (TF) parameters in subjects with signs and symptoms of dry eye disease (DED) using a novel nanometer resolution tear film imager (TFI, AdOM, Israel). In this prospective, cross-sectional observational study, TF parameters, including muco-aqueous layer thickness (MALT) and lipid-layer thickness (LLT), were assessed in 134 eyes of 79 subjects. All participants underwent an anterior segment examination to assess for clinical signs of DED. Subjects completed the ocular surface disease index (OSDI) questionnaire to assess symptoms of DED. Following exclusions, the final analysis included 60 eyes from 34 subjects. A Mann-Whitney test was used for statistical comparisons, with p < 0.05 considered statistically significant. Participants with clinical signs of DED demonstrated significantly lower mean LLT values (42.1nm + / − 13.6) compared to eyes without clinical signs of DED (64.1nm + / − 25.2), p < 0.001. Participants with symptoms of mild, moderate or severe DED had significantly lower mean MALT values (2,858nm + / − 911) compared to eyes without symptoms of DED (3,699nm + / − 1,184), p < 0.05. Our analysis of the human TF indicated that eyes presenting with signs of DED were associated with a thinner LLT, while symptomatic eyes were associated with a thinner MALT.